2002
DOI: 10.1002/polb.10215
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution and regeneration of cellulose in NaOH/thiourea aqueous solution

Abstract: A novel cellulose solvent, 1.5 M NaOH/0.65 M thiourea aqueous solution, was used to dissolve cotton linters having a molecular weight of 10.1 × 104 to prepare cellulose solution. Regenerated cellulose (RC) films were obtained from the cellulose solution by coagulating with sulfuric acid (H2SO4) aqueous solution with a concentration from 2 to 30 wt %. Solubility of cellulose, structure, and mechanical properties of the RC films were examined by infrared spectroscopy, X‐ray diffraction, scanning electron microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
198
0
11

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 297 publications
(217 citation statements)
references
References 27 publications
8
198
0
11
Order By: Relevance
“…For a given semicrystalline polymer, such as cellulose, the chains are more in the regular, arrangement and it is rather difficult to unfold the well-packed chains into a disordered state in solution (Lindman et al 2010;Medronho and Lindman 2014). Over decades the hydrogen bonds network in cellulose has been claimed as the reason of the crystalline structure of cellulose and the limitations in cellulose dissolution (Bodvik et al 2010;Zhang et al 2002), while the amphiphilic nature of cellulose has probably been underestimated (Medronho et al 2012. Thus, when developing efficient solvents for cellulose dissolution, not only the intermolecular hydrogen bonds need to be overcome, but also the hydrophobic chain interactions have to be minimized (Glasser et al 2012;Medronho et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For a given semicrystalline polymer, such as cellulose, the chains are more in the regular, arrangement and it is rather difficult to unfold the well-packed chains into a disordered state in solution (Lindman et al 2010;Medronho and Lindman 2014). Over decades the hydrogen bonds network in cellulose has been claimed as the reason of the crystalline structure of cellulose and the limitations in cellulose dissolution (Bodvik et al 2010;Zhang et al 2002), while the amphiphilic nature of cellulose has probably been underestimated (Medronho et al 2012. Thus, when developing efficient solvents for cellulose dissolution, not only the intermolecular hydrogen bonds need to be overcome, but also the hydrophobic chain interactions have to be minimized (Glasser et al 2012;Medronho et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Chen et al [76] have showed the effects of addition of urea, where a cotton linter pulp was dissolved and wet-spun into fibers, which reached comparable crystal orientation as rayon viscose fibers. Addition of thiourea in NaOH has also been shown to be a solvent of cellulose useful for fiber production [15]. Fibers produced from this solvent reached similar values for the mechanical properties as commercial fibers.…”
Section: Aqueous Alkalimentioning
confidence: 78%
“…These include sodium hydroxide (NaOH) at low temperatures without or with additives, such as urea, thiourea, and polyethylene glycol [13][14][15][16].…”
Section: Aqueous Mediamentioning
confidence: 99%
“…Out of~200 million tons of petroleum-derived Fig. 4 Sample of If -Then rules, scoring and reporting systems used in this work plastics produced globally, packaging proves to be the largest single market for plastics, amounting to over 12 million tons per year (Zhang et al 2002;Rhim and Ng 2007). Therefore, it is considered necessary for packaging materials to biodegrade in an acceptable time period after use to eliminate environmental waste disposal problems.…”
Section: Food Packaging Materialsmentioning
confidence: 99%